Keeping and Re-Finding Information On the Web: What Do People Do and What Do They Need To Do? - Bruce, Harry; Jones, William; Dumais, Susan (Proceedings of ASIST 2004, 2004)
This study (Keeping Found Things Found -KFTF) investigated the methods that people use in their workplace to re-access web information. People were observed using many different methods to keep web information for later use including the use of Bookmarks (or Favorites), self-addressed email, hand-written notes, and paper print-outs. Each keeping method provided a range of functions but none of the observed methods allowed for all desired functions. Participants in the KFTF study were also tested for their ability to return to a web site and several re-finding methods were observed and identified. When prompted with web site descriptions they had generated three to six months earlier, participants had a 95% or better success rate in returning to the cued-for web sites. Moreover, two thirds of these re-finding methods required no explicit keeping behavior. Common re-finding methods included the use of: 1.) A search service. 2.) Partial completion of a site's web address and acceptance of a suggested completion to this address (the auto-complete function). 3.) Hyperlinks from another web site. Results underline the importance of a reminding function. This paper also reports the data collected from a web survey conducted after the keeping and re-finding observations. 214 participants completed the survey. The data from the survey validated and elaborated the various methods that people use to keep web information for later re-use that were identified in earlier observational studies.